PENGARUH FINTECH PAYMENT DAN LITERASI KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN MAHASISWA UNIVERSITAS PAMULANG - Eka Priya Shifa; Vidya Amalia Rismanty (Bhinneka Multidisiplin Journal, 2026)
The purpose of this study is to determine the influence of Fintech payment and financial literacy on the financial management behavior of Pamulang University students. The method used is quantitative. The sampling technique uses saturated sampling where all members of the population are used as samples, thus the sample in this study totals 110 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The population in this study is students of the Faculty of Economics, Pamulang University and the number of saturated samples is 110 respondents. The method of data collection is through questionnaires with a likert scale, observation, and literature study. The results of this study are that Fintech payment has a significant effect on financial management behavior with a determinationcoefficient of 42.8% and the hypothesis test was obtained by calculating > table or (8,994 > 1,982). Financial literacy had a significant effect on financial management behavior with a determinationcoefficient of 62.7% and a hypothesis test obtained by calculating > ttable or (13,479 > 1,982). Fintech payment and financial literacy simultaneously had a significant effect on financial management behavior with a regression equation Y = 4.382 - 0.430X1 + 1.037X2, nii coefficient of determination was 64.7% while the remaining 35.3% was influenced by other factors. The hypothesis test obtained the value of Fcal > Ftabel or (98.147 > 3.08).